Functional polyoxometalates from solvothermal reactions of VOSO4 with tripodal alkoxides – a study on the reactivity of different "tris" derivatives. Issue 2 (14th December 2016) - Nachtigall, Olaf; Hagenbach, Adelheid; Wiecko, Jelena; Lentz, Dieter; Abram, Ulrich; Spandl, Johann
Abstract : A facile synthetic procedure for functional polyoxovanadates is reported. Furthermore, this study shows different possible binding modes of amino functionalised tris(hydroxymethyl)methane derivatives on polyoxovanadates. Abstract : We report a study on the structure directing effects of functional groups and counterions. The aim was to find a facile and high yielding synthetic procedure to obtain polyoxometalate (POM) building blocks for post-functionalisation. Therefore, solvothermal reactions of VOSO4 with various tris(hydroxymethyl)methane derivatives in alkaline methanolic solutions were investigated. In doing so, new POM fragments were isolated and characterised. The binding modes of the functionalised tripodal alkoxides turned out to be surprisingly different.